5 - √7 * (1 + 2√28)
= 5 - √7 * (1 + 2√4*7)
= 5 - √7 * (1 + 4√7)
= 5 - √7 - 4√49
= 5 - √7 - 28
= -23 - √7
Multiply and express in simplest radical form:
left bracket, 5, minus, square root of, 7, end square root, right bracket, left bracket, 1, plus, 2, square root of, 28, end square root, right bracket
3 answers
are you sure
Apologies for the mistake. Let's redo the calculation.
5 - √7 * (1 + 2√28)
= 5 - √7 * (1 + 2√(4*7))
= 5 - √7 * (1 + 2√(4)√(7))
= 5 - √7 * (1 + 2*2√7)
= 5 - √7 - 4√7
= 5 - 5√7
Therefore, the expression simplifies to 5 - 5√7.
5 - √7 * (1 + 2√28)
= 5 - √7 * (1 + 2√(4*7))
= 5 - √7 * (1 + 2√(4)√(7))
= 5 - √7 * (1 + 2*2√7)
= 5 - √7 - 4√7
= 5 - 5√7
Therefore, the expression simplifies to 5 - 5√7.